2022
DOI: 10.3390/nu14010206
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Feeding Infants and Toddler Study (OzFITS 2021): Breastfeeding and Early Feeding Practices

Abstract: The Australian Feeding Infants and Toddler Study 2021 (OzFITS 2021) is a nationwide survey of Australian caregivers’ infant and toddler feeding practices. Here, we describe breastfeeding rates and duration, use of breastmilk substitutes, and introduction of complementary (solid) foods, including common food allergens. Caregivers (n = 1140) were recruited by a digital marketing company and were interviewed using a structured telephone questionnaire to obtain information. Breastfeeding was initiated in 98% of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…Due to the high breastfeeding rate in the second year of life [ 10 ], we stratified the consumption of core food servings and discretionary foods by breastmilk intake on the day of the food record to determine if any differences in consumption patterns for breastfed and non-breastfed toddlers existed. On average, breastfed toddlers consumed less of the five good group foods than non-breastfed toddlers, which may have implications for nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high breastfeeding rate in the second year of life [ 10 ], we stratified the consumption of core food servings and discretionary foods by breastmilk intake on the day of the food record to determine if any differences in consumption patterns for breastfed and non-breastfed toddlers existed. On average, breastfed toddlers consumed less of the five good group foods than non-breastfed toddlers, which may have implications for nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we compare the number of daily servings of the five food groups and discretionary foods consumed by toddlers enrolled in the Australian Feeding Infants and Toddlers Study (OzFITS) 2021 to dietary patterns recommended in the Australian Dietary Guidelines [ 2 , 9 ]. Due to the high breastfeeding rates in the second year of life [ 10 ], we compared the intake of the five food groups and discretionary foods in breastfed and non-breastfed toddlers. We also report the percentage of energy derived from each food group and the contribution of beverages, including breastmilk, to total energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…The FITS studies that have been completed and published are shown in Table 1 [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These studies have been ongoing, and since 2002, there have been seven countries having published results, including the OzFITS studies now published in this Special Issue [ 4 , 5 , 6 , 7 , 8 ]. With each survey this is an opportunity to improve or modify the methodology yet stay consistent with a common analysis approach in more recent FITS such as those in Australia, China, Mexico, the Philippines, Russia, and the United States [ 3 , 4 ].…”
Section: Feeding Infants and Children Studies (Fits)mentioning
confidence: 99%
“…As shown in Table 1 , OzFITS is the latest FITS, and results are provided in four papers in this Special Issue [ 5 , 6 , 7 , 8 ] with a concluding paper [ 9 ]. These researchers indicated that national nutrition surveys conducted in Australia over the past 30 years had not included sampling of children under 2 years of age [ 5 ].…”
Section: The Australian Feeding Infants and Children Study (Ozfits)mentioning
confidence: 99%
See 1 more Smart Citation